2020
DOI: 10.30464/jmee.2020.4.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Optimum combination of machining parameters during drilling of Aluminium 7075 alloys using Grey based Taguchi approach

Abstract: From ancient days to till today manufacturing industries, especially making of holes on the parts during drilling process for precision assembling of parts facing problems with burr formation. Drilling operation is one of the finishing operation in the production cycle, removing of burrs during drilling process is a time consuming and non-value added process to the manufacturing sector. So reducing the size of burrs is the main aim of the present study. In the present work, optimization of burr size is conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Moreover, a low f and high point angle were suggested for attaining minimum surface roughness in the drilling of Al7075. In another study by Sreenivasulu and Rao [19], it was revealed that during the drilling of Al7075, the most influential parameters on burr height, thrust force, surface roughness, and circularity were f, point angle, and clearance angles, as compared to n and drill diameter. Kyratsis et al [20] concluded that tool diameter and f affected the thrust force and torque.…”
Section: Al6061 Al6351 Al7075mentioning
confidence: 98%
“…Moreover, a low f and high point angle were suggested for attaining minimum surface roughness in the drilling of Al7075. In another study by Sreenivasulu and Rao [19], it was revealed that during the drilling of Al7075, the most influential parameters on burr height, thrust force, surface roughness, and circularity were f, point angle, and clearance angles, as compared to n and drill diameter. Kyratsis et al [20] concluded that tool diameter and f affected the thrust force and torque.…”
Section: Al6061 Al6351 Al7075mentioning
confidence: 98%